The Relationship Between Blood Pressure and Sleep Quality in Patients At Tengku Rafi'an Siak Hospital - Amelia, Ami; Wanita, Deinike; Faisal, Faisal; Ristiani, Neni; Aulia, Risca; Sagita, Efan (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Sleep quality is a risk factor for hypertension. Chronic short sleep can cause hypertension due to an increase in the sympathetic nervous system and increased salt retention. This factors lead to structural adaptations in the cardiovascular system, causing high blood pressure. Blood pressure plays a critical role ini maintaining circulatiory system within the bloodstream. Blood pressure changes will have an impact on the body's homeostasis. Blood pressure is always needed to stimulate blood flow in the venous system, capillaries, arterioles, and arterie, thereby forming a continuous blood flow. Poor sleep patterns will result in poor blood pressure, which can lead to hypertension. Known as the silent killer, hypertension continues to be a global health concern. To analyze the relationship between blood pressure and sleep quality in Kabupaten Siak hypertensive patients. This research is analytical and observational, using a cross-sectional design. The population in this study was 774 polyclinic patients from January to November 2023 at the Tengku Rafi'an Regional General Hospital, Siak Regency. Meanwhile, the sample was 265 people taken using the Accidental Sampling technique. Data was taken using a questionnaire and then analyzed univariately and bivariately. The results p-value 0.018 0.05, so Ha is accepted, and H0 is rejected, which means there is a relationship between sleep quality and blood pressure in hypertensive patients. Meanwhile, the r value shows a result of 0.145, which means that the better the sleep quality of hypertensive patients, the more blood pressure will return to normal. There is a relationship between blood pressure and sleep quality in Kabupaten Siak hypertensive patients. The more restful sleep you get, the faster your blood pressure will return to normal.